Analysis of empirical method for predicting maneuverability of ultra-large container ship using Maneuvering Modelling Group (MMG) model - Zeinurrohman, Rangga; Trimulyono, Andi; Wicaksono, Ardhana; Hadi, Eko Sasmito; Samuel, Samuel; Hakim, Muhammad Luqman; Purwanto, Dedi Budi (Universitas Mercu Buana, 2024)
International Maritime Organization (IMO) provided manoeuvrability standards for all ships above 100 m to ensure the ship's safety and surroundings. In the preliminary design stage, one way to ensure a ship's manoeuvrability under IMO standards is to use empirical methods that are cheaper and less time-consuming than model tests. Empirical methods used analysis regression to develop their formula from the model test result database, and their formula depends on ship hull parameters and dimension ratios such as , , , and . However, the database of the existing empirical formulas is limited to small-medium merchant ships and fishing vessels, as consequences for larger ships are inaccurate and have a significant error in predicting ship manoeuvres. This study modified the existing empirical formulas by adding specified ship data into the existing database and analyzing the accuracy of predicting ship manoeuvres using the Maneuvering Modelling Group (MMG) model. We verify by adding the selected ship data into the existing database, which shows improvement in predicting ship manoeuvres. The modified formulas show improvement by only giving 5% RMSE of tactical diameter and 3% RMSE of ship advance in turning manoeuvre, and this is a 78% overall improvement in predicting the turning motion of ultra-large container ships compared to previous formulas. The quantitative and qualitative produce better estimation result that indicates the right track to derive the empirical formulas for Ultra-Large Container ships.